Position specific peak running demands, and influence of bout type in professional rugby union - Glassbrook, D. J.; Williams, L. D.; McShane, K. J. (PLOS ONE, 2025)
Objectives To quantify peak running intensity in professional rugby union across position groups, and peak running intensity differences between bout types (i.e., whole, starter, substitute).